Exploring the Influence of Subjective Norms, Personal Naturalism, and Social Impacts on Female Consumers Green Purchase Intentions - Chrisniyanti, Ayu; Saputra, Kadek Surya Adi (JUSTBEST Journal of Sustainable Business and Management, 2024)
This study aims to identify factors that influence attitude woman towards green products, with a focus on subjective norms, personal naturalism, and environmental impacts. social. Working women beginner aged 21-30 years in Bali who consume green products are the samples in this study. The method used is approach quantitative with descriptive research design correlational. Data were collected using questionnaire that was measured with Likert scale, which was then analyzed using SPSS for validity, reliability, and regression tests multiple. The results of the study show that subjective norms and personal naturalism have influence significant to attitude woman towards green products (p < 0.05), while the impact social although positive, does not show influence significant in a way statistics. This study provides important insights for marketers in designing green product marketing strategies with emphasize support social and sustainability values. These findings also enrich theory behavior planned with integrate factor social and psychological in purchasing green products.